SISTEM INFORMASI GEOGRAFIS BERBASIS WEB UNTUK PEMETAAN JALAN DAN BANGUNAN (studi kasus : Bidang Tata Ruang Dinas Pekerjaan Umum Kabupaten Kubu Raya) - Agung Sasongko (Universitas Bina Sarana Informatika, 2016)
Supervision and control of construction of buildings in the region is one of the tasks of the Spatial field in the Public Works department. In an effort to decision-making tools necessary in the form of map visualizations that can quickly determine the position of buildings and roads, so as to give a quick overview to the field of Spatial Planning to give a decision, whether or not a building may be established in consideration of the surrounding environment. Current information technology has made it possible to provide visual information in the form of map making it easier to understand. Current map information can be accessed online together, thus providing a transparent inforamsi to many people. To improve services in the field of Spatial Public Works Department Kubu Raya then needed a Geographic Information System Roads and Buildings for building data collection and facilitate their efforts to control the construction of the buildings by the community. Development of systems using the Software Development Life Cycle waterfall model. Library used for OpenLayers map visualization is based javascript. The data collected is stored in a database that has been installed PostgreSQL PostGIS for spatial data management.